PERAN BADAN NARKOTIKA NASIONAL SUMATRA UTARA DALAM MENGATASI PENGGUNA NARKOBA (RESIDIVIS) - Roma Esi Sihaloho, Roma; Nurmaya R A Simanjuntak , Nurmaya (Cattleya Darmaya Fortuna, 2025)
Recidivism is a major concern in the criminal justice system, which occurs when a person returns to commit a crime after serving a sentence or rehabilitation. In the case of narcotics crimes in Indonesia, the high recidivism rate reflects weaknesses in law enforcement and the ineffectiveness of rehabilitation programs. Recidivism involves factors such as environmental stress, substance addiction, and lack of social support. Prisons play a role not only as a place of punishment, but also as a forum for coaching so that inmates can improve themselves and return to society with positive behavior. However, rehabilitation for narcotics recidivists faces various complex obstacles. This study aims to identify the main causative factors of recidivism in the National Narcotics Agency of North Sumatra Province and formulate effective prevention strategies through rehabilitation to support policy development and preventive efforts in reducing the rate of narcotics recidivism in the region.